2021
DOI: 10.3390/ijms22052349
|View full text |Cite
|
Sign up to set email alerts
|

Affinity Maturation of a T-Cell Receptor-Like Antibody Specific for a Cytomegalovirus pp65-Derived Peptide Presented by HLA-A*02:01

Abstract: Human cytomegalovirus (CMV) infection is widespread among adults (60–90%) and is usually undetected in healthy individuals without symptoms but can cause severe diseases in immunocompromised hosts. T-cell receptor (TCR)-like antibodies (Abs), which recognize complex antigens (peptide–MHC complex, pMHC) composed of MHC molecules with embedded short peptides derived from intracellular proteins, including pathogenic viral proteins, can serve as diagnostic and/or therapeutic agents. In this study, we aimed to engi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
(109 reference statements)
0
5
0
Order By: Relevance
“…For plasmids of peptide-fused Abs, including TEDbodies, DNA encoding the peptide and a G 4 S linker was subcloned in-frame without additional sequences at the C-terminus of the HC of each Ab. Expression plasmids for the anti-EGFR Ab necitumumab [26] and TCRlike Ab C1-17 [27] have been described previously. For the anti-programmed cell death protein 1 (PD1) Ab pembrolizumab (Keytruda ® ) and anti-OX40 (CD134) 1166/1167 Abs, DNA fragments of VH and VL of pembrolizumab (DrugBank Accession No.…”
Section: Expression and Purification Of Tedbodies And Absmentioning
confidence: 99%
See 2 more Smart Citations
“…For plasmids of peptide-fused Abs, including TEDbodies, DNA encoding the peptide and a G 4 S linker was subcloned in-frame without additional sequences at the C-terminus of the HC of each Ab. Expression plasmids for the anti-EGFR Ab necitumumab [26] and TCRlike Ab C1-17 [27] have been described previously. For the anti-programmed cell death protein 1 (PD1) Ab pembrolizumab (Keytruda ® ) and anti-OX40 (CD134) 1166/1167 Abs, DNA fragments of VH and VL of pembrolizumab (DrugBank Accession No.…”
Section: Expression and Purification Of Tedbodies And Absmentioning
confidence: 99%
“…For the detection of CMV-pMHCI on the cell surface at 37 °C, the indicated cells (1.5 × 10 5 ) were seeded in a 12-well plate in the medium containing 10% FBS and cultured until they were fully attached to the bottom of the plates (~ 12 to 15 h). Next, the cells were treated for 18 h with a synthetic peptide, TEDbody, or control Ab at the indicated concentrations, washed with PBS, and stained with the CMV-pMHCI-specific C1-17 Ab (10 nM) [27] in a blocking solution [PBS (pH 7.4) and 2% FBS] for 1 h at 4 °C. After a wash with the ice-cold blocking solution, the cells were stained with an Alexa Fluor 647-labeled rabbit antimouse IgG Ab (Thermo Fisher Scientific) for 30 min at 4 °C.…”
Section: Flow Cytometrymentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, target cells must express the peptide of interest in the context of a specific MHC class I variant, as engineered TCR recognizes both peptide and MHC class I molecules. Accordingly, TCR-based treatments focus on relatively abundant MHC class I alleles, such as HLA-A*02:01 [23]. Tumor targeting TCR sequences can be identified via isolation and deep sequencing strategies of tumor infiltrating lymphocytes (TILs).…”
Section: Targeting Intracellular Proteinsmentioning
confidence: 99%
“…The approval of this biologic verified TCR-based protein engineering as a valuable therapeutic modality. Lee et al reported a TCR-like antibody specific for HLA-A*02:01 in complex with a peptide derived from human cytomegalovirus (CMV) pp65 protein [ 2 ]. The binding affinity was matured by sequential mutagenesis of complementarity-determining regions using yeast surface display technology for its application to the diagnostics and therapeutics of CMV infection.…”
mentioning
confidence: 99%